A visual response to the siege of Sarajevo. (3rd April 2019) - Coldwell, Paul
ABSTRACT: This paper considers art works made by the author over a gap of twenty years in response to the siege of Sarajevo (1992–1996). The first works were inspired by the then BBC War Correspondent, Martin Bell in his radio broadcast of 1996 in which he reflected on the tragedy of the Bosnian War. The second group of works were made as part of the AHRC funded project Art & Reconciliation and were the result of visiting Sarajevo for the first time in 2018. For this the author drew upon his experience of using collections and archives as source material, here drawing from the collection of the Museum of History in Sarajevo where the final exhibition was staged. The author reflects on the role of the artist in tackling issues of conflict when not an eyewitness and draws parallels with examples such as Michael Tippet's oratorio A Child of Our Time and Bob Dylan's The Lonesome Death of Hattie Carroll . The paper also considers how knitting can be used to construct a form of alternative memorial and how his own personal experiences and memories can form the foundations for new work.